UNSUR-UNSUR INTRINSIK CERITA PENDEK â€œPROTESâ€ KARYA PUTU WIJAYA - LAUMA, ATHAR (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2017)
ABSTRACTThe purpose of the research is to get an idea of the elements of the literary work which is contained in the short stories of protest.To analyze the intrinsic elements are used structural approach according to Teeuw (1984) research results obtained among others. 1. The main theme of the short story is social criticism 2. The short story flows are confidential 3. The time background of the place plays well. It can be concluded that the relationship between the elements in the short story